A 70 pc Diameter Nova Superremnant Surrounding the Recurrent Nova RS Ophiuchi - Michael M. Shara; Kenneth M. Lanzetta; Alexandra Masegian; James T. Garland; Stefan Gromoll; Alexei Kniazev; Lee Townsend; David Zurek; Joanna Mikolajewska; David Valls-Gabaud; Frederick M. Walter; John K. Webb (The Astronomical Journal, 2025)
Recurrent novae undergo thermonuclear-powered eruptions separated by less than 100 yr, enabled by subgiant or red giant donors transferring hydrogen-rich matter at very high rates onto their massive white dwarf companions. The most rapidly moving parts of envelopes ejected in successive recurrent nova events are predicted to overtake and collide with the slowest ejecta of the previous eruption, leading to the buildup of vast (∼10–100 pc) superremnants surrounding all recurrent novae, but only three examples are currently known. We report deep narrowband imaging and spectroscopy, which have revealed a ∼70 pc diameter shell surrounding the frequently recurring nova RS Ophiuchi. We estimate the superremnant mass to be ∼20–200 M _⊙ , expanding at a few tens of km/s, with an age of order 50–100 kyr. Its extremely low surface brightness and large angular size help explain the hitherto surprising absence of nova superremnants. Our results support the prediction that all recurrent novae are surrounded by similar extended structures.